Bifidobacterium adolescentis-derived nicotinic acid improves host skeletal muscle mitochondrial function to ameliorate sarcopenia - Zeng Zhang; Quan Guo; Zhihan Yang; Yukai Sun; Shuaiming Jiang; Yangli He; Jiahe Li; Jiachao Zhang (Cell Reports)
Summary: Sarcopenia significantly diminishes quality of life and increases mortality risk in older adults. While the connection between the gut microbiome and muscle health is recognized, the underlying mechanisms are poorly understood. In this study, shotgun metagenomics revealed that Bifidobacterium adolescentis is notably depleted in individuals with sarcopenia, correlating with reduced muscle mass and function. This finding was validated in aged mice. Metabolomics analysis identified nicotinic acid as a key metabolite produced by B. adolescentis, linked to improvements in muscle mass and functionality in individuals with sarcopenia. Mechanistically, nicotinic acid restores nicotinamide adenine dinucleotide (NAD+) levels in muscle, inhibits the FoxO3/Atrogin-1/Murf-1 axis, and promotes satellite cell proliferation, reducing muscle atrophy. Additionally, NAD+ activation enhances the silent-information-regulator 1 (SIRT1)/peroxisome-proliferator-activated-receptor-γ-coactivator 1-alpha (PGC-1α) axis, stimulating mitochondrial biogenesis and promoting oxidative metabolism in slow-twitch fibers, ultimately improving muscle function. Our findings suggest that B. adolescentis-derived nicotinic acid could be a promising therapeutic strategy for individuals with sarcopenia.